2002
DOI: 10.1016/s0014-5793(02)03093-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of transcription and induction of programmed cell death by human p53‐family members p63 and p73

Abstract: The p53 tumor suppressor acts as a transcription factor and has a central function in controlling apoptosis. With p63 and p73 two genes coding for proteins homologous to p53 have been identi¢ed. We describe the properties of seven human p63 and p73 proteins as transcriptional activators of p21WAF1/CIP1 expression and apoptotic inducers in direct comparison to p53 in the same assay systems employing DLD-1-tet-o¡ colon cells. Programmed cell death is detected in cells expressing high levels of p53 and p73K K. Ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
74
1

Year Published

2004
2004
2008
2008

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 39 publications
7
74
1
Order By: Relevance
“…As controls and consistent with previous observations mRNA levels for known p53 target genes like p21 WAF1/CIP1 and mdm2 were found to be upregulated and previously described targets like cyclin A, Cyclin B, cdk1 and cdc25C were downregulated [25]. Furthermore, under the experimental conditions employed changes in expression of p53 target genes precede the changes due to impending apoptosis [17]. Following the microarray analysis as an indicator, we confirmed the p53-dependent decrease of the Cks2 mRNA levels by real-time RT-PCR quantification in two independent experiments yielding an average of 10.1-fold downregulation of Cks2 mRNA.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…As controls and consistent with previous observations mRNA levels for known p53 target genes like p21 WAF1/CIP1 and mdm2 were found to be upregulated and previously described targets like cyclin A, Cyclin B, cdk1 and cdc25C were downregulated [25]. Furthermore, under the experimental conditions employed changes in expression of p53 target genes precede the changes due to impending apoptosis [17]. Following the microarray analysis as an indicator, we confirmed the p53-dependent decrease of the Cks2 mRNA levels by real-time RT-PCR quantification in two independent experiments yielding an average of 10.1-fold downregulation of Cks2 mRNA.…”
Section: Resultssupporting
confidence: 90%
“…3B). Moreover, we had found p73a, p73b, TAp63c and TA * p63c able to activate transcription from a p21 WAF1/CIP1 reporter [9,17]. This confirms them to be transcriptionally active but unable to alter expression from the Cks2 promoter.…”
Section: Expression Of P73 or P63 Proteins Does Not Altersupporting
confidence: 56%
“…Regulatory pathways that involve isoforms of the p53 family members p63 and p73 may be involved. The latter regulate Waf1 mRNA expression (Dietz et al, 2002), and their participation may explain the partial p53 dependence in the observed DPI-induced G 1 checkpoint (Figure 6b). Regardless, our data show that ATM is as responsive to change in the cellular redox environment as it is to DNA damage.…”
Section: Discussionmentioning
confidence: 97%
“…A potential mechanism regulating this process might be through p63, which has been shown to activate transcription of p21. 5,6 Further, p63 is also known to induce expression of Jagged1 7 which is involved in Notch signaling and osteoclastogenesis. 8 p63 is a member of the gene family that includes p53 and p73.…”
mentioning
confidence: 99%